SEJARAH STRATEGI PERLUASAN WILAYAH PRAJA MANGKUNEGARAN PADA MASA KEKUASAAN MANGKUNEGARA I & II - Lucia Arter Lintang Gritantin (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2024)
R.M. Said (Mangkunegara I), the founder of Praja Mangkunegaran (Dukedom Mangkunegaran) was famous for his persistent character and strong willingness to expand Dukedom Mangkunegaran’s territory. He passed his disposition on to his successor, Mangkunegara II. These two figures have the same mission regarding territorial expansion. Having strong work ethics and integrity was seen as an added value by the Dutch East Indies Government. Therefore, the colonial government gave them many privileges, especially in regards to the granting and distribution of land. The author sees this phenomenon as an interesting research topic. Therefore, it is necessary to record steps and analyze strategies used by Mangkunegara I & II in expanding the territory of Dukedom Mangkunegaran